Additional notes on Sclerolinum brattstromi (Pogonophora) and the establishment of a new family Sclerolinidae - Webb, Michael (Sarsia, 1964)
Sclerolinum brattstromi inhabits various types of decaying wood, old pieces of rope, and was found on old pieces of cardboard and leather. The body terminates in a multisegmental structure without setae or terminal sucker but with metamerically arranged septa dividing the coelom into serially arranged coelomic pouches. Because of the obvious differences between this genus and all other known Pogonophora a new family, Sclerolinidae, is proposed to accommodate the two known species, sibogae (Southward, 1961) and brattstromi (Webb, 1964c). It is not possible to place this family in either of the orders, but the opinion expressed is that it might form a separate order.Sclerolinum brattstromi inhabits various types of decaying wood, old pieces of rope, and was found on old pieces of cardboard and leather. The body terminates in a multisegmental structure without setae or terminal sucker but with metamerically arranged septa dividing the coelom into serially arranged coelomic pouches. Because of the obvious differences between this genus and all other known Pogonophora a new family, Sclerolinidae, is proposed to accommodate the two known species, sibogae (Southward, 1961) and brattstromi (Webb, 1964c). It is not possible to place this family in either of the orders, but the opinion expressed is that it might form a separate order.
Annelidabase